Roy Henry Vickers 'Indigenous Environmental Justice' - Pugh, Ryan (Simon Fraser University, 2015)
Disclaimer: All testimonies are the experiences and beliefs of the individuals interviewed. Interviewee: Vickers, Roy Henry|Interviewe: Pugh, Ryan|Oral Testimony Archivists: Weasal Bear, Robyn and Harrison, Don|Principle Investigator:Dr. annie ross.